A study of effectiveness of training and development toward employees in Sapura Industrial Berhad / Normazura Mohd Zainy - Mohd Zainy, Normazura (Faculty of Business and Management, 2011)
This thesis presents a study, which has sought to the effectiveness of training and development toward employees in Sapura Industrial Berhad and at the same time identifies the purpose of training and development toward employees. Besides that, this thesis is about to identifying the factors which is organizational support, employee’s attitude and transfer of training that contribute to the effectiveness of training and development toward employees. Training and development are most important role in enhancing and increasing the developmental and performance of employees. Through training and development, employees can learn new thing and improved their work performance better. It is noteworthy to investigate how the factors contribute to the effectiveness of training and development toward employees. A survey was conducted through distribution of questionnaires to the employees from different background profile of Sapura Industrial Berhad. A total of 40 respondents self-administered questionnaire were distribute and collected simultaneously, which have resulted 100% response rate. Using Statistical Package for Social Science (SPSS), the data was computed and analyzes based on the effectiveness of training and development. The result is in the form of reliability test, frequency and correlation. The result indicates that there are significance relationship between all the factor which is organizational support, employee’s attitude and transfer of training with the effectiveness of training and development toward employees in Sapura Industrial Berhad.